Validity and reliability of wireless pressure insoles for measuring gait biomechanics in healthy adults: A protocol for a systematic review and meta-analysis - Tomasz Cudejko; Mohammad Al-Amri; Sylwia Szotek; Magdalena Żuk; Magdalena Kobielarz; Kristiaan D’Août (PLoS ONE, 2025)
Wireless pressure insoles are emerging as portable, unobtrusive tools for gait analysis in both clinical and real-world settings. These systems incorporate pressure sensors and often inertial measurement units (IMUs), allowing for the collection of spatiotemporal, kinetic, and foot-level kinematic data. Although widely adopted, the measurement properties of wireless pressure insoles—specifically their concurrent validity and test–retest reliability—have not been systematically evaluated. This protocol outlines the methods for a systematic review and meta-analysis that will synthesise the current evidence on the psychometric properties of wireless pressure insoles during walking in healthy adults. This protocol follows the PRISMA-P 2015 guidelines and is registered in the Open Science Framework. We will include peer-reviewed journal articles that assess either the concurrent validity (i.e., simultaneous collection with a gold-standard comparator) or test–retest reliability (e.g., between-day, within-day, or between-rater reproducibility) of wireless pressure insoles during level walking in healthy adults (≥18 years). Outcomes of interest include spatiotemporal, kinematic and kinetic parameters. A comprehensive literature search will be conducted across MEDLINE, CINAHL, Scopus, Web of Science, SPORTDiscus, IEEE Xplore. Screening will be performed independently by two reviewers. Data extraction will follow a pre-piloted template and study quality will be assessed by two independent reviewers using a modified version of the Critical Appraisal of Study Design for Psychometric Articles. Where appropriate, meta-analyses will be conducted using random-effects models, with effect sizes (r, ICC) pooled and heterogeneity assessed via I 2 . This review will provide a comprehensive synthesis of the concurrent validity and test–retest reliability of wireless pressure insoles in healthy adults, offering valuable insights for researchers, clinicians, and technology developers. While methodological heterogeneity may affect the scope of synthesis, the findings will help guide future research and clinical applications.